Essential oils encapsulation performance evaluation: a review on encapsulation parameters / Siti Afiqah ‘Aisyah Murtadza …[et al.] - Murtadza, Siti Afiqah ‘Aisyah; Jai, Junaidah; Md Zaki, Nurul Asyikin; Hamzah, Fazlena (Universiti Teknologi MARA, 2021)
Application of essential oils (EOs) in food preservation and products is not a virgin trend owing to its bio-functional properties such as antioxidants, antimicrobials, medicinal values, and aromatic functionalities. However, EOs are prone to degrade upon exposure to different environmental surroundings, eventually losing their bio-functional activities and limits their potential applications. Hence, encapsulation process is introduced to overcome this issue. In order, to evaluate encapsulation process, there are several key indicators, known as encapsulation parameters, that reflects the performance of encapsulation process and quality of encapsulation products (encapsulates) namely encapsulation efficiency, encapsulation yield, payload/loading capacity, and surface loading. Since some terms are used interchangeably across literatures, problems arise when it comes to compare these parameters among published works as there is no specific guideline or specific term to classify these parameters. Therefore, this paper aims to help researchers understand an insight of the definition of encapsulation parameters used in evaluating performance of encapsulation process and encapsulation products of EOs. Commonly used evaluation techniques as well as some recommendations for considerations are also highlighted. Different calculation formulae used in evaluating encapsulation performance would have significant difference to the encapsulation parameters values.